A comprehensive species sampling sheds light on the molecular phylogenetics of Calothecinae (Poaceae, Pooideae, Poeae): Evidence for a new subtribe and multiple genera within the Chascolytrum clade. Issue 3 (5th July 2021) - da Silva, Leonardo N.; Saarela, Jeffery M.; Essi, Liliana; de Souza‐Chies, Tatiana T.
Abstract: The circumscription of the grass subtribe Calothecinae has undergone several changes since its description. Currently, it comprises Chascolytrum and the recently described genera Laegaardia and Paramochloa . Here we evaluate the circumscription of Calothecinae and the recently proposed infrageneric classification of Chascolytrum based on a phylogeny with more comprehensive taxon and molecular marker sampling than in previous studies. We sampled all Calothecinae genera, all but one Chascolytrum species, two South American Trisetum s.l ., and representatives of the subtribes Agrostidinae, Brizinae, Echinopogoninae, Koeleriinae, Phalaridinae, and Torreyochloinae within Poaceae tribe Poeae. We performed Bayesian and Maximum Likelihood analyses of four plastid DNA regions ( atpF‐atpH, matK, rps16 intron, and trnL‐trnF ) and two nuclear ribosomal regions (ITS and ETS). Our results revealed that neither Calothecinae nor Chascolytrum is monophyletic, as currently recognized, because Trisetum brasiliense and Trisetum bulbosum are nested within Chascolytrum . We include these two Trisetum species in Calothecinae as incertae sedis . Laegaardia and Paramochloa form a clade that is sister to the Chascolytrum + Trisetum clade, and based on morphological characters, we transfer the former to the new subtribe Paramochloinae. Our Chascolytrum phylogeny is better resolved and supported than in previous studies, and based on these results, we divide Chascolytrum into nine genera, including two new ones: Boldrinia (gen. nov.), Calotheca, Chascolytrum, Erianthecium, Lombardochloa, Microbriza, Poidium, Rhombolytrum, and Rosengurttia (gen. nov.). We provide a key to Calothecinae genera, descriptions of the genera, nomenclatural information, and keys to species of each genus. In addition, six new combinations are proposed. Abstract : The first comprehensive phylogenetic hypothesis for Calothecinae reveals that neither the subtribe nor the genus Chascolytrum is monophyletic. On the basis of the phylogenetic results and morphological cohesiveness, we propose a new subtribe and split C hascolytrum into nine smaller genera, of which two are newly described.